Climate walking: A comparison study of mobile weather stations and their relevance for urban planning, design, human health and well-being - T. Silva; R. Ramusga; M. Matias; J. Amaro; A. Bonifácio; C. Reis; A. Chokhachian; G. Lopes; A. Almeida; J. Frazão; J. Vasconcelos; A. Lopes; et al. (City and Environment Interactions)
Microclimate conditions affect the outdoor urban way of life for humans. These conditions directly impact people’s health and well-being, such as access to medical care or a healthy lifestyle. Human thermal comfort is paramount for people’s health, both physical and mental. In this paper, the study compares two microclimate mobile weather stations (MWS) based on a set of users’-based assessment criteria (usability, user-friendliness, sensors) and thermal comfort (UTCI) results accuracy. The comparison was carried out through continuous mobile transect measurements lasting an hour and a half, conducted on two summer days in Lisbon across distinct urban morphological settings. This research was developed to assist future researchers in urban climatology with the design of microscale studies, particularly in relation to equipment selection, performance assessment, and methodological procedures. In terms of performance, we found the RMSE to be 1.3 °C for air temperature, 1.6 % for relative humidity, 1.3 m/s for wind speed, and 8.4 W/m2 for solar radiation for MWS 1, and 1.5 °C for air temperature, 2.9 % for relative humidity, 1.5 m/s for wind speed, and 11.6 W/m2 for radiation for MWS 2. Both MWS units exhibited a consistent performance, however, MWS 1 demonstrated greater overall accuracy, particularly in the measurement of air temperature, relative humidity, and wind speed. Differences were also observed between the sensors of MWS 1 and MWS 2, as well as in the MWS usability, factors which may be significant depending on the users’ objectives and available resources. Despite this, both MWS units were deemed suitable for deployment in urban environments, with MWS 2 offering a more intuitive user experience. The findings of this study are particularly relevant for those beginning mobile meteorological measurements, as well as for researchers aiming to address urban heat stress and enhance public well-being and thermal comfort through their work. However, the study is limited by its short duration and geographic scope, and further research is needed to expand its applicability to diverse urban settings.